Limited open repair for achilles tendon rupture in the setting of co-morbidities: A case series and technique review - James C. Connors, DPM, FACFAS; Mark A. Hardy, DPM, FACFAS; Halle L. Krebs; Ali A. Manji, DPM; Cory M. Jarosi, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases)
An acute Achilles tendon rupture poses a difficult treatment strategy in both young and old patients. Commonly considered an injury of the middle aged “weekend warrior,” an Achilles tendon tear in a sedentary patient is quite debilitating. An open surgical repair has many advantages including direct tendon visualization as well as the ability to interlock the suturing technique. Unfortunately, the extensive incision needed for proper tendon exposure creates a tenuous scenario primed for an increased risk of complications. The classic surgical incision disrupts the paratenon, the main blood supply to the watershed area of the tendon at the rupture site which is the weakest point of the repair. The minimal subcutaneous layer between the distal skin incision and the tendon has notoriously been a site of dehiscence. An infection in this area spreads quickly along the tendon planes with devasting consequences. These grave complications have led to a paradigm shift in repair techniques. Minimally invasive procedures utilize a percutaneous jig suturing system placed through a small incision at the site of rupture. Unfortunately, a distinct set of complications are associated with blind placement of fiber wire including sural nerve entrapment and incomplete tendon capture in the repair technique. A new technique merges the advantages of a small incision with the ability to directly visualize the tendon repair. The paratenon is maintained at the rupture site while being able to utilize an asymmetric offset classic suturing technique to add strength to the repair.